The effects of a calf pump device on second half performance of a simulated soccer match in competitive youth players. Issue 6 (19th March 2019) - Béliard, S.; Cassirame, J.; Ennequin, G.; Coratella, G.; Tordi, N.
ABSTRACT: During soccer matches, performance decrements have been reported that relate to both physical abilities and technical skills. To investigate the effects of low-frequency electrical stimulation LFES (VeinoplusSport®, Ad Rem Technology, France) administered during half-time recovery on performance alterations during the second half. Twenty-two highly trained young players undertook a soccer-match simulation (SAFT 90 ). During half-time, they were randomly assigned to LFES group or Placebo group. Each half was split into 3 bouts of 12 minutes. Following each bout, maximal strike speed (MSS), sprint test (ST), maximal sprint accelerations (MA) and metabolic power (MP) were determined in both groups. Arterial (AF) and venous flows (VF) were measured at rest and at the end of half-time. LEFS group exhibited beneficial effects on performance compared to the Placebo group with a likely effect for MSS, ST, MA, and a possible effect for MP. AF and VF increased statistically more in LEFS group compared to Placebo group. The use of specific calf-pump LFES during half-time of a youth simulated soccer match attenuated the decrease in performance during the second half compared to Placebo group. This effect is most marked at the beginning of the second half with regards to explosive parameters.